Challenges in MR‐only seed localization for postimplant dosimetry in permanent prostate brachytherapy. Issue 10 (11th September 2017) - Zijlstra, Frank; Moerland, Marinus A.; van der Voort van Zyp, Jochem R.N.; Noteboom, Juus L.; Viergever, Max A.; Seevinck, Peter R.
Abstract : Purpose: An MR‐only postimplant dosimetry workflow for low dose rate (LDR) brachytherapy could reduce patient burden, improve accuracy, and improve cost efficiency. However, localization of brachytherapy seeds on MRI scans remains a major challenge for this type of workflow. In this study, we propose and validate an MR‐only seed localization method and identify remaining challenges. Methods and materials: The localization method was based on template matching of simulations of complex‐valued imaging artifacts around metal brachytherapy seeds. The method was applied to MRI scans of 25 prostate cancer patients who underwent LDR brachytherapy and for whom postimplant dosimetry was performed after 4 weeks. The seed locations found with the MR‐only method were validated against the seed locations found on CT. The circumstances in which detection errors were made were classified to gain an insight in the nature of the errors. Results: A total of 1490 of 1557 (96%) seeds were correctly detected, while 67 false‐positive errors were made. The correctly detected seed locations had a high spatial accuracy with an average error of 0.8 mm compared with CT. A majority of the false positives occurred near other seeds. Most false negatives were found in either stranded configurations without spacers or near other seeds. Conclusions: The low detection error rate and high localization accuracy obtained by the complex‐valued template matching approach are promising for future clinical application of MR‐only dosimetry. The most important remaining challenge is robustness with regard to configurations of multiple seeds in close vicinity, such as in strands of seeds without spacers. This issue could potentially be resolved by simulating specific configurations of multiple seeds or by constraining the treatment planning to avoid these configurations, which could make the proposed method competitive with CT‐based seed localization.